1997
DOI: 10.1016/s0304-3975(96)00171-5
|View full text |Cite
|
Sign up to set email alerts
|

Infinitary lambda calculus

Abstract: In a previous paper we have established the theory of transfinite reduction for orthogonal term rewriting systems. In this paper we perform the same task for the lambda calculus. From the viewpoint of infinitary rewriting, the Bohm model of the lambda calculus can be seen as an infinitary term model. In contrast to term rewriting, there are several different possible notions of infinite tc1m, which give rise to different Bohm-like models, which embody different notions of lazy or cager computation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
183
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(187 citation statements)
references
References 4 publications
4
183
0
Order By: Relevance
“…a lambda-calculus with letrec, seq, case, constructors, and por, which is equipped with a normal order reduction and a contextual semantics as definition of equality of expressions. First it defines the infinite trees corresponding to the unrolling of expressions as in the 111-calculus of [5] also adding constructors, case, seq and por. Then reduction on the infinite trees is defined, where the basic rules are the corresponding rules for (beta), seq, case and por, and the rule ∞ − → is a generalization of the (parallel) 1-reduction (see [2]); it can also be seen as an infinite development (see also [5]), however, the tree structure is a bit more general for LRCCPλ.…”
Section: Structure and Results Of This Papermentioning
confidence: 99%
See 2 more Smart Citations
“…a lambda-calculus with letrec, seq, case, constructors, and por, which is equipped with a normal order reduction and a contextual semantics as definition of equality of expressions. First it defines the infinite trees corresponding to the unrolling of expressions as in the 111-calculus of [5] also adding constructors, case, seq and por. Then reduction on the infinite trees is defined, where the basic rules are the corresponding rules for (beta), seq, case and por, and the rule ∞ − → is a generalization of the (parallel) 1-reduction (see [2]); it can also be seen as an infinite development (see also [5]), however, the tree structure is a bit more general for LRCCPλ.…”
Section: Structure and Results Of This Papermentioning
confidence: 99%
“…First it defines the infinite trees corresponding to the unrolling of expressions as in the 111-calculus of [5] also adding constructors, case, seq and por. Then reduction on the infinite trees is defined, where the basic rules are the corresponding rules for (beta), seq, case and por, and the rule ∞ − → is a generalization of the (parallel) 1-reduction (see [2]); it can also be seen as an infinite development (see also [5]), however, the tree structure is a bit more general for LRCCPλ. It is shown that convergence of expressions in the call-by-need lambda-calculus, as well as for the call-by-name calculus is equivalent to convergence of a normal-order-variant of (Tr)-reduction, i.e.…”
Section: Structure and Results Of This Papermentioning
confidence: 99%
See 1 more Smart Citation
“…In nitary λ-calculus has been introduced independently by Berarducci [3] and by Kennaway et al [16].…”
Section: B More Details On In Nitary λ-Calculimentioning
confidence: 99%
“…). In nitary λ-calculi have been considered in the literature [3,15,16,4,8] both to study in nite structures arising from lazy functional languages or to study consistency problems in the standard λ-calculus. Though, in nitary λ-calculi have been designed in a much di erent way from the in nitary calculus underlying Λµ-calculus: whereas in those frameworks, a reduction sequence may have trans nite length, terms have a (possibly in nite) depth which is bounded by ω.…”
Section: Introductionmentioning
confidence: 99%